Application of Magnetic Field on Aged Rice Seeds Toward the Vegetative Growth of Rice (Oryza sativa L.) Variety Inpari 32 HDB - Fauzi, Ibnu Nur; Saputri, Dwijowati Asih; Listiana, Ika (Biospecies, 2026)
Rice is the most important agricultural commodity in Indonesia. As a staple food, rice contains carbohydrates, protein, and other nutrients essential for the human body. The level of rice consumption in Indonesia is relatively high, which must be balanced by increased production. One way to improve yields is through the use of high-quality seeds. However, rice seeds available on the market are often past their shelf life (aged), resulting in decreased seed viability and negatively affecting plant growth. Therefore, efforts are needed to improve the quality of aged seeds. This study aimed to examine the effect of exposure to a magnetic field with an intensity of 0.2 mT on the vegetative growth of aged rice seeds of the Inpari 32 HDB variety. The research was conducted at the Botany Laboratory of the University of Lampung and in Lumbirejo Village, Pesawaran Regency, from July to September 2024. The study used a Completely Randomized Design (CRD) with four magnetic field exposure treatments: 3 minutes 54 seconds, 7 minutes 48 seconds, 11 minutes 42 seconds, and a control group with no exposure, observations were conducted for 8 weeks or 56 days after planting and were made every two weeks. The parameters observed included leaf area, number of leaves, rice tiller height, number of tillers, fresh weight and dry weight of the shoot, and wet weight and dry weight of the root. The research results showed that exposure to a 0.2 mT magnetic field only caused an effect during the early growth phase (2 weeks after planting) in several parameters such as leaf number, plant height, and number of tillers. However, this effect did not continue in the subsequent vegetative phase. Other parameters like leaf area and biomass did not show significant differences between treatments. Thus, the magnetic field at this intensity does not provide a stable influence on the vegetative growth of rice.